Depression profile in cancer patients and patients without a chronic somatic disease - Nikendei, Christoph; Terhoeven, Valentin; Ehrenthal, Johannes C.; Maatouk, Imad; Wild, Beate; Herzog, Wolfgang; Friederich, Hans-Christoph (Psycho-oncology, 2018)
To investigate whether depressed oncology patients show a specific depressive symptom profile, we compared depression symptoms in depressed cancer patients (CANCER-DEP) and depressed patients without a chronic somatic disease (NONCANCER-DEP).